2022
DOI: 10.3390/fermentation8070304
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and Methane Production from Anaerobic Co-Digestion of Sorghum and Cow Manure: Effect of pH and Hydraulic Retention Time

Abstract: The need for alternative energy sources is constantly growing worldwide, while the focus has shifted to the valorization of biomass. The aim of the present study was to determine the optimal pH and hydraulic retention time (HRT) values for treating a mixture of sorghum biomass solution with liquid cow manure (in a ratio 95:5 v/v) through anaerobic digestion, in a two-stage system. Batch tests were initially carried out for the investigation of the pH effect on bio-hydrogen and volatile fatty acids (VFA) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…This VFA/alkalinity ratio could serve as an indicator of the buffering capacity of the system, as the increase in VFAs and a decline in alkalinity signifies a diminished pH buffer capacity. Generally, a maximum threshold VFA/alkalinity ratio of 0.6 is considered suitable to maintain a healthy AD process without the risk of acidification [ 19 ]. Therefore, the high VFA/alkalinity ratio could potentially emerge as a critical factor contributing to the instability observed in the 20-days HRT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This VFA/alkalinity ratio could serve as an indicator of the buffering capacity of the system, as the increase in VFAs and a decline in alkalinity signifies a diminished pH buffer capacity. Generally, a maximum threshold VFA/alkalinity ratio of 0.6 is considered suitable to maintain a healthy AD process without the risk of acidification [ 19 ]. Therefore, the high VFA/alkalinity ratio could potentially emerge as a critical factor contributing to the instability observed in the 20-days HRT.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the high VFA/alkalinity ratio could potentially emerge as a critical factor contributing to the instability observed in the 20-days HRT. In contrast, it was observed that the VFA/alkalinity ratio, between 0.63 and 0.64, detected within the HRTs of 40, 30 and 25 days, stayed within a range that closely aligns with favorable conditions (0.6) [ 19 ]. This observation is consistent with previous research that indicated a VFA/alkalinity ratio of 0.6, which was detected at the optimal HRT and resulted in effective biogas production from biogas effluent and filter cake [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These correlations were similar to those observed in the study by Dareioti et al (2022), who found that at a lower HRT of 20 days, the process showed evidence of inhibition and/or overload, such as an accumulation of VFAs and a decline in MPR and MY. Moreover, the maximum MPR and MY of 0.44 L-CH 4 /L•d and 295.3 mL-CH 4 /g-VS added, respectively, were obtained at the HRT of 25 days [30]. Likewise, Ramos and Silva (2020) reported an increased MPR with a higher OLR achieved by reducing HRT to the optimal level in a two-stage hydrogen and methane production process from sugarcane silage in a sequential fluidized bed reactor [31].…”
Section: Second-stage Methane Production From Hydrogenic Effluent In ...mentioning
confidence: 88%
“…In the process of producing methane, most bacteria prefer a neutral pH. Kornaros et al [70] experimented with the AcoD of CM and sorghum aimed at studying the infuence of initial pH value on CH 4 and H 2 production in a two-stage digester. Tey achieved the highest H 2 yield of 0.92 mol H 2 /mol carbohydrates consumed at pH 5.…”
Section: Hydraulic Retention Time and Temperaturementioning
confidence: 99%